Pengaruh Whistleblowing System, Bystander Effect, dan Anti-fraud Awareness terhadap Pencegahan Fraud dalam Pengelolaan Dana Desa pada Kabupaten Sijunjung - Utari Dwi Putri; Efrizal Sofyan (Universitas Negeri Padang, 2023)
This study intends to examine the impact of the bystander effect, anti-fraud awareness, and the whistleblowing system on managing village money in Sijunjung Regency and preventing fraud. This study is quantitative in nature. The Slovin formula is used to determine how many sample members there should be. A total of 117 respondents from 39 villages in the Sijunjung district made up the study's sample. The hypothesis in this study was tested using multiple linear regression analysis with SPSS version 20. The results showed that the whistleblowing system and anti-fraud awareness had a positive effect on fraud prevention, while the bystander effect had a negative effect on fraud prevention.